The Two-in-One : Walking with Smokie, Walking with Blindness. - Michalko, Rod (Animals, culture, and society., 2011)
When Rod Michalko's sight finally became so limited that he no longer felt safe on busy city streets or traveling alone, he began a search for a guide. The Two-in-One is his account of how his search ended with Smokie, a guide dog, and a dramatically different sense of blindness. Few people who regularly encountered Michalko in his neighborhood shops and cafes realized that he was technically blind; like many people with physical disabilities, he had found ways of compensating for his impairment. Those who knew about his condition thought of him as a fully realized person who just happened to.